Analisis Kebutuhan Pengembangan Media Pembelajaran Berbasis Technological, Pedagogical, And Content Knowledge (Tpack) Untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Nurhasanah, Fia Aprillia; Herlina Usman (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to analyze and identify the needs of elementary school students for learning media used in learning mathematics. This research method uses Research and Development with the ADDIE approach. The stages of this approach begin with analyzing the needs of mathematics learning media, learning media design, learning media development, implementation and evaluation. In the needs analysis using research objects 30 elementary school students and class teachers. The data collection techniques used are observation, interviews and questionnaires. This research produces learning media products in the form of Audio visual media in the form of learning animations based on (Technological, Pedagogical, Content, Knowledge) TPACK. The research tools consist of material expert validation instruments, media expert validation instruments, teacher validation instruments and student and teacher questionnaires. The media used by researchers can be used as learning media in elementary schools.